Dollar a Day Revisited - Ravallion, Martin (World Bank, Washington, DC, 2012)
The paper presents the first major update of the international "$1 a day" poverty line, first proposed in 1990 for measuring absolute poverty by the standards of the world's poorest countries. In a new data set of national poverty lines we find that a marked economic gradient only emerges when consumption per person is above about $2.00 a day at 2005 purchasing power parity. Below this, the average poverty line is $1.25, which we propose as the new international poverty line. Relative poverty appears to matter more to developing countries than has been thought. The authors' proposed schedule of relative poverty lines is bounded below by $1.25, and rises at a gradient of $1 in $3 when mean consumption is above $2.00 a day.